IMPLEMENTASI METODE FUZZY SUGENO UNTUK MENENTUKAN BESARAN DANA ANGGARAN PEMBUATAN ALAT PEMECAH BATU ATAU STONE CRUSHER PADA CV.PRAJI TEHNIK - Yuda Perwira (Jurnal Mantik Penusa, 2019)
Problems in the Selection of manpower during this time is done with a system that has not been computerized, so the process of selecting labor is slow. Often the error of the selection of candidates so that the workforce received less skilled and not in accordance with the wishes of the company. Design of a computerized decision support system Quality workforce using Fuzzy Weighted Product (F-WP) is expected to replace the old system. By using the criteria that are changed in the form of weight assessment so that the system can perform calculations that provide the speed of information in the form of a computerized system. Decision support system provides results in the form of information printed in the form of reports containing data of prospective workers based on the highest value to the lowest value, thus providing convenience for companies to hire quality labor.